(untitled) (Medical Forum Monthly, 2021)
Objective: The management and assessment of anemia is poorly understood in Balochistan. To determine frequency of anemia associated with chronic kidney disease patients admitted in Tertiary Care Hospital at Quetta Balochistan. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Medicine Department Sandeman Provincial Hospital Quetta, from January, 2019 to June, 2019 for a period of six months. Materials and Methods: 106 patients who met the diagnostic criteria were included. Mean age in our study was 48.38±7.89 years. Mean duration of CKD in our study was 3.89±1.66 days. Results: Out of 106 patients who developed chronic kidney disease patients, 26 (24.52%) had anemia and 80 (75.47%) did not have anemia. The data result shows that the anemia due to chronic kidney disease was more in male 18(16.98%) as compared to female patients 8(7.54%). Frequency distribution of age showed that 06 (5.66%) were in age group 30-40 years, 12 (11.32%) patients were in age group 41-50 years and 8 (7.54%) patients were belonging to age group 51-60 years with anemia in chronic kidney disease. The anemic patient’s distribution in different stage of CKD showed that, 02 (1.88%), 3(2.83%), 6 (5.66%), 8 (7.54%) and 7 (6.60%) were in CKD stage 1, 2, 3, 4 and 5 respectively. Conclusion: Anemia arise severe problems of chronic kidney disease. Correction of anemia may improve renal and is a significant middle marker of CKD so it might be valuable to measure hemoglobin even at overall screening. Early discovery of CKD is of highest position to stop the development of renal failure.